Loosening detection of the femoral component of hip prostheses with extracorporeal shockwaves: a pilot study - Rieger, Johannes Sebastian; Jäger, Sebastian; Kretzer, Jan Philippe; Rupp, Rüdiger; Bitsch, Rudi G. (Medical engineering & physics, 2015)
The diagnosis of aseptic loosening of hip implants is often challenging. A vibrational analysis of the bone-implant interface could be an alternative method to analyze the fixation of endoprostheses. We assessed an innovative and new approach for excitation by using extracorporeal shockwaves in this study. In three cadaver specimens total hip arthroplasty was performed bilaterally. Four different states of implant loosening were simulated. Three accelerometers were fixed at the medial condyle, the greater trochanter, and the crest of the ilium. The bone-implant compound was excited with highly standardized extracorporeal shock waves. Resonance spectra between 100 Hz and 5000 Hz were recorded. This technique permitted a good adaptation to varying soft tissue conditions. The main resonance frequency of the hip joints occurred at about 2000 Hz. The analysis of the measured spectra showed an interrelation between the state of loosening and the frequency values of the resonances. In case of a stem loosening, there were significant shifts of the resonance into the lower frequency area between 386 Hz and 847 Hz. With this novel technique the degree of stem loosening could be assessed in a soft tissue considering configuration. This study forms a first step for future establishment of a non-invasive, non-radiological and fast applicable diagnostic procedure for early detection of endoprostheses loosening before manifest presence of clinical signs.